Beaded leg bands - Unidentified artist (Colorado State University. Libraries, 2016)
Two wini leg bands.
This item was part of an exhibition at the Avenir Museum of Design and Merchandising titled Kuna Molas: Sewn Stories and the Interplay of Tradition and Change, August 18, 2014-July 31, 2015.
Beaded leg bands in orange, green, pink, and black beads.
Keywords: Molas -- Panama; Beadwork -- Panama